Homeless for the First Time in Later Life: Uncovering More Than One Pathway. (29th January 2018) - Burns, Victoria F; Sussman, Tamara
Abstract: Background and Objectives: Increasingly, researchers have recognized the heterogeneity with the growing population of older homeless adults. However, scant research has considered the complex pathways into first-time homelessness from the perspective of older adults themselves. Research Design and Methods: Through in-depth interviews, this constructivist grounded theory study aimed to address this gap by exploring the pathways of 15 adults, aged 50 years and older, into late-life homelessness. Results: Two divergent pathways were revealed: gradual and rapid. Individuals with gradual pathways endured many years of struggle related to poor housing conditions, lack of social support, and social distress. They had reached out for support on several occasions, with little success due to their limited social capital. In contrast, for individuals with rapid moves to homelessness, multiple unanticipated losses threatened their economic and social resources and they were propelled into homelessness with little warning. Despite having access to social networks to help buffer these losses, they preferred homelessness over asking for help and being perceived as dependent. Discussion and Implications: Our study revealed that different pathways into homelessness require divergent strategies of prevention and support. For individuals with gradual moves, strengthening pre-homeless social supports and addressing social distress may have mitigated the eventual loss of housing. For individuals with rapid pathways, homelessness may have been prevented if independence and self-sufficiency were less idealized in our society.